The Legal Analysis of the Strength of Proof of Underhanded Deeds Legalized by a Notary - Saepullah, Saepullah (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to analyze: 1) Deed under the hand in civil evidence law. 2) The legal consequences of applying the Underhand Deed are in accordance with Article 15 paragraph (2) letter a of the UUJN or Article 1874a of the Civil Code. This thesis uses a normative legal research type which is descriptive analytical. Secondary legal materials in the form of books, and tertiary in the form of general dictionaries, legal dictionaries. The results of the study: 1) The private deed in civil evidence law is a weak evidence. The deed under the hand must be signed and sufficient stamp duty if there is no signer then it can be categorized only as an ordinary letter. 2) As a legal consequence of the existence of two different underhanded deeds, namely Article 15 paragraph (2) letter a of the UUJN and Article 1874 of the Civil Code, there has been legal uncertainty. As a result of the private deed applied by a Notary as referred to in Article 15 paragraph (2) letter a of the UUJN, the deed has the power of formal proof of truth guaranteed by the Notary so that the private deed is not included in the category of weak evidence. As a result of a private deed applied by a Notary as referred to in Article 1874a of the Civil Code, the deed has the power of formal and material proof of truth.Keywords: Deed; Proof; Underhand.